Vrikshayurved Methods for Disease Control in Plants with Special Reference to Onion (Allium Cepa) - More Shweta Vinod; Avalaskar Amit D; Mahajan Vijay; Sogam Onkar Anant (International Journal of Ayurveda and Pharma Research, 2021)
Introduction- In today’s era due to modernization and civilization people follows modern techniques of cultivation which is starting from seed viability study then for nursery adding fertilizers in land and for treating disease and fulfilling their nutrients value adding or spraying chemical fertilizers which leads to hazards effect in environment on every creature. Aacharyas found natural solutions for every plant issue many years back they already mentioned in Vrikshayurved, how to diagnose and treat different kind of plant diseases more naturally and authentically. Objective- This article aims to diagnose and treat plant diseases according to Vrikshayurved. Materials and methods- Study performed on Onion seedlings (Allium cepa) under the observation of Directorate of Onion and Garlic Research Institute, Rajgurunagar, Pune. Onion seedlings were treated by Kunap jal and Madhuyastyadi Kwath. Disease of Onion seedlings were diagnosed and treated by Vrikshayurved methods using Kunap jal and Madhuyashtyadi Kwath. Results- The Vrikshayurved methods showed around 80-85% reduction in curling of leaves, 100% reduction in yellowish discoloration, 100 % reduction in dryness of leaves. Vrikshayurved intervention improved growth rate drastically. Conclusion- Vrikshayurved intervention improved curling, dryness and yellowish discoloration of leaves significantly. It also doubled growth rate of the onion seedlings. It indicates that Vrikshayurved methods are applicable in today’s era.